A study of sciatic nerve in relation to piriformis muscle in South Indian population - Bajpe, Roshni; N. S., Ashray; Sheshachalam Bharadwaj, Anagha (International Journal of Research in Medical Sciences, 2025)
Background: The sciatic nerve (SN) is the largest nerve in the body, emerging from the pelvis beneath the piriformis muscle (PM) and dividing into the tibial nerve (TN) and common peroneal nerve (CPN). The long course and proximity to the PM make the SN susceptible to multiple injuries and compression, especially in the gluteal area and posterior thigh. Methods: This study aimed to assess the anatomical variations of the SN course by analysing 68 lower limb specimens. The dissection focused on the gluteal region and back of the thigh, with special attention to the level and nature of the SN’s bifurcation. The SN and PM were exposed by retracting the gluteus maximus muscle. The level of SN division and its relation to PM were recorded, photographed and classified into five groups. Results: The findings showed a wide range of variations in SN bifurcation, with the most common type of SN bifurcation occurring at the lower end of the posterior thigh, found in 72.05% of specimens. The least common was the pelvic bifurcation before exiting the gluteal region in 2.94% of specimens. The study also revealed rare variations, such as the reunion of split divisions in 8.82% of specimens. Conclusions: The variations in the division of the SN are crucial for clinical and surgical procedures involving the gluteal and posterior thigh regions. Such anatomical insights can reduce iatrogenic injuries and improve procedural outcomes.